MINAT PENGEMBANGAN KOPERASI TANI PADA KOMUNITAS USAHA TANI PADI SAWAH DI KECAMATAN CIKEDUNG - Hermanto Hermanto; Lukman Effendi; Tassim Billah (Sekolah Tinggi Pariwisata Mataram, 2020)
The research studied the interest of farmers' development in the development of resource resource units, using 81 respondents associated with the cooperative. The study uses linear regression analysis and descriptive analysis, data collection using a questionnaire using the likert scale. There are successful free variables of individual characteristics, external factors and cooperatives, all three of the free variables set down to a few of the change indicators to see how they affect the fixed variables. In a descriptive analysis of the age of respondents, the average is in older categories with a percentage of more than 50%, the average education of 9-15 years (SMA-PT), the latest is very high at 7-18 and 38-56 years. The average farmer's land area has a fork of 0.9-35 ha (0.9-35 ha). From regression analysis results in the multiple can an X1 characteristic variable not having any significance to free variables only one indicator has an influence that is the attempting farm experience. The external X2 variables from analysis had an impact on the interest of farmers' development with three of the indicators of five that had significant value to the fixed variables. Successful X3 variable cooperatives can have an effect on fixed variables. Value for determining strategies to increase interest by using a computer-and-count t analysis.